India's developing villages - Madan, G.R. (New Delhi, 1990)
The book India's Developing Villages makes a comprehensive and critical survey of rural development programmes going on in the Indian villages at present. The book has been divided into several parts to deal with various aspects of village life in a systematic manner. In part one is discussed the history of rural development in India. Part two deals with programmes of agricultural development which include the production of various crops; credit, supplies and marketing; land reforms; land holding and management; irrigation and power; animal husbandry; transport and communication. Part three deals with the problems of rural workers and rural industries including the problems of poverty, unemployment and Minimum Needs Programme. Part four deals with rural institutions, including the cooperative move ment; Panchayati Raj; religious institutions; caste system; joint family system; rural leadership, etc. Part five is concerned with rural welfare services. These include education, health and family planning, housing and social welfare, services for the weaker groups such as children, women, youth, Backward Classes, etc. Part six deals with the relations between rural reconstruction and planning and discusses in outline the Five Year Plans. Part seven gives a critical appraisal of rural development programmes going on in villages since the launching of community develop ment programme in the country on October 2, 1952.
Keywords: Rural development India